THE DRUG-FASTNESS OF SPIROCHETES TO ARSENIC, MERCURIAL, AND IODIDE COMPOUNDS IN VITRO - Akatsu, Seinai (The Rockefeller University Press, 1917)
In the foregoing experiments we attempted to determine whether or not, by subjecting several varieties of spirochetes to increasing doses of certain chemotherapeutic agents, a gradual increase of resistance to the latter could be shown. For this purpose, pure cultures of Treponema pallidum, Treponema microdentium, and Spirochœta refringens were used against the action of salvarsan, neosalvarsan, bichloride of mercury, and iodine-iodide potassium solution in vitro. For culture media, the usual ascites-broth-tissue medium as well as solid ascites-agar-tissue medium was used. After permitting the spirochetes to grow for a fortnight in media containing certain quantities of each drug, transfers were made from tubes showing various degrees of growth to the next series of tubes containing the same drug in still higher concentrations, and similar transfers repeated every 2 weeks. The results of the experiments may be briefly summarized as follows: 1. Treponema pallidum and Treponema microdentium have, within 3 to 4 months, increased their tolerance to salvarsan and neosalvarsan to five and one-half times their original mark. With Spirochata refringens the increase was about three times. 2. Against the action of bichloride of mercury, the amount of increased tolerance of Treponema pallidum was about 35 to 70 times the original, while that of Treponema microdentium was about 10 times as much and was reached within 10 weeks. Spirochata refringens resisted 30 times the original dose. 3. There was an unmistakable increase of resistance of these spirochetes to the action of the iodine-iodide solution (Lugol's solution) when they were grown for several generations in fluid media containing the iodine solution, but the rate of increase between the initial and the acquired tolerance was slight. In general, the addition of Lugol"s solution to fluid media has a weak inhibitory influence upon the growth of the spirochetes, requiring for the total suppression of growth a quantity of over 0.7 cc. to 5 cc. of the culture media. The tolerance reached was for about three times that amount. 4. A similar tolerance phenomenon has not been established when employing a solid instead of a fluid medium containing the drugs. No explanation is offered except a suggestion that the drugs held in the agar do not enter into combination with certain tissue constituents of the medium as they are able to do with tissue elements in fluid media. This may be a factor necessary for inducing drug tolerance in these organisms in vitro. 5. The increased drug-fastness in vitro has a limit beyond which no further advance can be made. This limit varies with different species of spirochetes. 6. The acquired drug-fastness in vitro gradually disappears when the spirochetes are cultivated again in the drug-free media for several generations.